Pediatric MR lung imaging with 3D ultrashort‐TE in free breathing: Are we past the conventional T2 sequence?. Issue 12 (13th September 2021) - Gräfe, Daniel; Anders, Rebecca; Prenzel, Freerk; Sorge, Ina; Roth, Christian; Benkert, Thomas; Hirsch, Franz Wolfgang
Abstract: Objectives: Magnetic resonance imaging (MRI) of the lungs is challenging for several reasons, mainly due to the respiratory motion, low proton density, and rapid T2* decay. Recent MR sequences with ultrashort TE (UTE) coupled with respiratory compensation promise to overcome these obstacles. So far, there are very few studies on the relevance of these sequences in children. The aim of the study was to compare the diagnostic value of a respiratory‐self‐gated three‐dimensional UTE sequence versus a conventional respiratory‐triggered T2‐weighted turbo spin echo (T2‐TSE) sequence in a pediatric collective. Study Design: Seventy‐one patients between 0 and 18 years of age, who were scheduled for a thoracic MRI based on diverse clinical indications, were examined on a 3T MRI system. The UTE and T2‐TSE sequences were evaluated by two readers regarding quality features and visualization of eight common pathology patterns. Results: The image quality of both sequences was equally high, with UTE depicting pleural and central bronchi more clearly. In pathologies, UTE was superior to T2‐TSE for so‐called "MR‐negative pathologies", significant for air trapping, and in tendency for bullae and cysts. In all remaining pathologies, T2‐TSE proved to be at least equivalent to UTE. Conclusions: At present, UTE cannot serve as a universal replacement for conventional T2‐TSE for all pathologies. It yields, however, a substantial benefit in the context of hyperinflation, emphysema, cysts, or pathologies of the bronchial system.